Book review: Systems Metabolic Engineering. Issue 5 (7th January 2013) - Alper, Hal S.
<x xml:space="preserve">Abstract</x> Systems Metabolic Enginering, edited by Christoph Wittmann and Sang Yup Lee "sits at the crossroads of being an introductory book providing an overview of the field and a handy desk‐reference for state‐of‐the‐art case studies for the expert metabolic engineer". Read this book review by Hal Alper. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>